Polaryzacyjno-optyczna metoda wyznaczania składowych płaskiego stanu naprężenia w obszarze plastycznym - A. Litewka (Engineering Transactions, 1969)
The paper contains a description of the polarization-optical method which makes it possible to delimitate the elastic region from the plastic one, and to determine the components of the plane state of stress in the plastic region. The method is based on the measurement of four quantities during the investigations: the orders of the isochromatic fringe patterns m1 and m2 for two mono-chromatic light sources with wavelengths λ1, and λ2, the parameter of the isoclines 0 and the dispersion of double refraction D. These quantities are used for the direct calculation of the sum, difference and directions of the main stresses, as well as for determination of the plastic region as the locus of points with the value D = 0. As an example of the application of this method is presented the determination of the distribution of stresses in an infinite disk with a circular opening stretched unidirectionally in infinity. The results obtained are compared with those obtained by means of the Frocht method and with the theoretical solution.